Produksi Film Pendek âIn Soloâ Berbasis Multimedia - Irawan, Indra; Purnama, Bambang Eka; Urbani, Yunan Hepy (Fakultas Teknologi Informatika Universitas Surakarta, 2014)
ABSTRACT : The development of cinema at the University of Surakarta now had enough amount with the theme of the movie is varied, there are themed documentary, romance, education, and others. Movie called